Efficiency of electron cooling in cold-electron bolometers with traps - Pimanov, Dmitrii A; Frost, Vladimir A; Blagodatkin, Anton V; Gordeeva, Anna V; Pankratov, Andrey L; Kuzmin, Leonid S (Beilstein journal of nanotechnology, 2022)
Electron on-chip cooling from the base temperature of 300 mK is very important for highly sensitive detectors operating in space due to problems of dilution fridges at low gravity. Electron cooling is also important for ground-based telescopes equipped with 3 He cryostats being able to function at any operating angle. This work is aimed at the investigation of electron cooling in the low-temperature range. New samples of cold-electron bolometers with traps and hybrid superconducting/ferromagnetic absorbers have shown a temperature reduction of the electrons in the refrigerator junctions from 300 to 82 mK, from 200 to 33 mK, and from 100 to 25 mK in the idle regime without optical power load. The electron temperature was determined by solving heat balance equations with account of the leakage current, sixth power of temperature in the whole temperature range, and the Andreev current using numerical methods and an automatic fit algorithm.